Acceleration of electrons by a laser pulse at its output onto an optical surface of the vacuum – transparent medium interface. Laser synchrotron. (May 2016) - Romanovskiy, M.Yu.
Abstract: We consider the electron dynamics in the field of an electromagnetic wave produced at the vacuum – transparent medium interface upon reflection from the boundary, close to total internal reflection. The propagation velocity of a constant phase of the electromagnetic wave along the interface can vary from to infinity ( is the speed of light in vacuum, and is the refractive index of the medium at the interface). In this case, there emerge regions of positive and negative phases of the field with wavelengths, approximately equal to half the wavelength of the original laser beam, which can propagate at a speed close to that of light in vacuum. If a beam of relativistic electrons propagates along the surface, they can gain energy and accelerate, as well as radiate. With closed trajectories of electron motion, a laser synchrotron will be implemented as a result of many acceleration cycles.